Mechanisms of Methane Hydrate Formation in Geological Systems. (16th October 2019) - You, K.; Flemings, P.B.; Malinverno, A.; Collett, T.S.; Darnell, K.
Abstract: Natural gas hydrate is ice‐like mixture of gas (mostly methane) and water that is widely found in sediments along the world's continental margins and within and beneath permafrost and glaciers in a near‐surface depth interval where the pressure is sufficiently high and temperature sufficiently low for gas hydrate to be stable. We categorize the myriad of geological gas hydrate deposits into five characteristic types. We then review the multiple quantitative models that have proposed to describe the genesis of these deposits and describe how each may have formed. We emphasize the importance of coupling multiphase flow (free gas and liquid water) and multicomponent reactive transport with geological history to describe the dynamical processes of gas hydrate formation and evolution in geological systems. A better insight into the kinetics of methane formation from microbial biogenesis and the processes of multiphase flow at the pore scale will advance our knowledge of how these systems form. By understanding the generation and evolution of gas hydrate through time, we will better decipher the role of gas hydrate in the carbon cycle, its potential to contribute to climate change and geohazards, and how to design optimal strategies for gas production from hydrate reservoirs. Plain Language Summary: Scientific drillings and geophysical investigations have revealed various occurrences of gas hydrate under the seafloor and within and beneath permafrost. We summarize their key features and categorize their occurrences into five major types. We then review the different quantitative models that have been developed to explain their formation in the field and link different models to field observations. We identify the key advances achieved, the major remaining challenges, and the efforts required to further understand the formation of gas hydrate in geological systems. This knowledge can help us learn the role of gas hydrate in natural environments. Key Points: Geological gas hydrate deposits can be categorized into five major types and tied to six different formation mechanisms Free gas flow and capillary pressure play significant roles in forming many concentrated hydrate deposits A better understanding of microbial methanogenesis will illuminate how methane hydrate deposits are formed in geological systems